COMPETITIVITATEA – CRITERIU FUNDAMENTAL AL STRATEGIEI DEZVOLTĂRII ECONOMICE DURABILE, CONDIŢIE A SUCCESULUI PE PIAŢĂ - Hămuraru, Maria; Pascal, Cristina (CEP USM, 2010)
The article highlights the conceptual and practical significance definition of competitiveness, which in current conditions of economic transformation is a fundamental criterion of sustainable economic development strategy of the country. The increase of national competitiveness requires the most efficient allocation of available resources and creating new resources, which will lead to better performance in external trade and thus a higher market share globally, which entails an increased yield investment and ultimately will lead to prosperity and security of the Republic of Moldova.
Keywords: competitivitatea; Indicele Competitivităţii Globale (ICG)